Prostitute, victim, survivor, woman: examining the discursive structures surrounding women in sex trafficking situations - Taylor, Julie Lynn, author; Broadfoot, Kirsten J., advisor; Griffin, Cindy L., committee member; Coke, Pamela K., committee member (Colorado State University. Libraries, 2010)
Within the realm of sex trafficking, the discourse that describes women often floats between naming the women as victims or as agents. To be an agent assumes that women are complying prostitutes. To be a victim assumes that the women are being put in the situation against their will. Significantly, the perpetrator rarely is discussed. Moreover, in most descriptions, the woman is described as the lone actor in the rape and its aftermath. Interviews were conducted with four different organizations within Colorado that understand and describe sex trafficking situations in unique ways. Through the interview data, discursive connections and discrepancies were illuminated, allowing for the researcher to follow the flow of discourse among organizations. In this study, the consequences of these descriptions, and their impact on voice, agency and space of action, are examined.
Department Head: Sue Pendell.